2018
DOI: 10.1002/ece3.4777
|View full text |Cite
|
Sign up to set email alerts
|

Identifying spawning sites and other critical habitat in lotic systems using eDNA “snapshots”: A case study using the sea lamprey Petromyzon marinus L.

Abstract: Many aquatic species of conservation concern exist at low densities and are inherently difficult to detect or monitor using conventional methods. However, the introduction of environmental (e)DNA has recently transformed our ability to detect these species and enables effective deployment of limited conservation resources. Identifying areas for breeding, as well as the ecological distribution of species, is vital to the survival or recovery of a conservation species (i.e., areas of critical habitat). In many s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
54
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(58 citation statements)
references
References 49 publications
4
54
0
Order By: Relevance
“…River kilometer has been found to be a strong predictor of relative abundance for larval E. tridentatus (Torgersen & Close, ). While a link between eDNA concentration and density requires enumerating individuals, which was beyond the scope of our study, several studies covering diverse aquatic species have observed positive relationships between eDNA concentration and biomass/density (Bracken et al, ; Doi et al, ; Lacoursiere‐Roussel et al, ; Pilliod et al, ; Takahara et al, ; Thomsen et al, ; Wilcox et al, ), supporting our conclusion that E. tridentatus eDNA concentrations within each river reflected a density gradient.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…River kilometer has been found to be a strong predictor of relative abundance for larval E. tridentatus (Torgersen & Close, ). While a link between eDNA concentration and density requires enumerating individuals, which was beyond the scope of our study, several studies covering diverse aquatic species have observed positive relationships between eDNA concentration and biomass/density (Bracken et al, ; Doi et al, ; Lacoursiere‐Roussel et al, ; Pilliod et al, ; Takahara et al, ; Thomsen et al, ; Wilcox et al, ), supporting our conclusion that E. tridentatus eDNA concentrations within each river reflected a density gradient.…”
Section: Discussionsupporting
confidence: 86%
“…Entosphenus tridentatus adults migrate into freshwater in summer and fall (Beamish, 1980;Keefer, Moser, Boggs, Daigle, & Peery, 2009) and hold in overwintering habitats until they begin their spawning migration in spring. Positive relationships between eDNA concentration and adult density have been observed in Sea Lamprey (Petromyzon marinus Linnaeus, 1758) (Bracken et al, 2019;Schloesser et al, 2018), and, therefore, would likely be observed in adult E. tridentatus also. We observed no adult E. tridentatus at the time of electrofishing and it is unknown if adults were present at the time when eDNA samples were collected.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, an eDNA assay using water samples was developed to identify key spawning areas for sea lamprey, including an investigation of the impact of physical barriers that prevent the species fully utilizing its potential spawning habitat (Bracken et al, 2019). Whilst useful for mapping the spatial distribution of spawning areas, the utility of the tool is limited by the short temporal window during which spawning occurs.…”
Section: Discussionmentioning
confidence: 99%
“…Correspondingly, the application of eDNA detection to monitoring biodiversity is now well established, with a broad range of applications, including species detection in either an ancient or contemporary context, from the reconstruction of past faunal or floral assemblages to the identification of range expansions / biological invasions (Bohmann et al, 2014). In the freshwater environment, it has been used to document habitat utilisation, detect the presence of rare and invasive species, and quantify spawning activity in pre-defined areas (Bracken, Rooney, Kelly□Quinn, King, & Carlsson, 2019; Stoeckle, Soboleva, & Charlop-Powers, 2017; Thomsen & Willerslev, 2015b), including the extent of upstream spawning migrations in anadromous fish species (Antognazza et al, 2019).…”
Section: Introductionmentioning
confidence: 99%